Asian Development Bank sustainability report 2020. (Metro Manila, Philippines Asian Development Bank, 2020)
Produced every 2 years, the report aims to enable stakeholders to understand and assess ADB sustainability performance. It includes information on how ADB operations are curbing emissions; promoting resource use efficiency; expanding green, blue, and climate financing, increasing investments in clean energy, and much more. This 2020 report consists of two parts. Part I: Highlights, presents key sustainability information in a highly visual format using infographics, and Part II: The Global Reporting Initiative (GRI) Content Index, details ADB sustainability approaches against GRI reporting standards.
Keywords: Public administration -- Cost effectiveness; Climatic changes -- Government policy; Electronic books